Enhancing gender responsiveness of technical and vocational education and training in Vietnam. (ADB briefs., 2020)
The Government of Viet Nam has introduced policies to strengthen TVET programs in a move to meet the demands of the labor market for skilled human resources. While TVET reforms and programs are intended to be gender-responsive, data show that the participation of men and women are still affected by stereotypes and biases among other factors. The issues and recommendations presented in this brief are based on a report and assessment focusing on the gender responsiveness of TVET and school-to-work transition in Vietnam.